Infant immunization coverage in a colombian poor municipality in the post-conflict era (2022)
Colombia has an expanded program of immunization of >22 biologics mainly for younger than 6 years old. We aimed to estimate vaccination coverage in children under 6 years old in San Jacinto (Bolivar), in a post-conflict and COVID-19 pandemic scenario. We conducted a cross-sectional survey from October to November of 2021, in a Caribbean municipality of Colombia (24,910 population) mostly affected by the armed conflict. A two-stage cluster sampling was used with a precision of 5.5% and a design effect of 2, considering a non-response rate of 20%. We collected data on immunization record cards and other basic sociodemographic information from surveys of caregivers of children. Absolute and timely-vaccine coverages adjusted by age were. Out of 187 surveyed children, 159 (85.3%) had vaccination card. BCG (tuberculosis) vaccine had the greater coverage (99,3%), followed by Hb, pentavalent, and polio (>98%). All biologics showed absolute coverages greater than 90%, except for yellow fever (82.6%) and 5-year boosters (70% for MMR [measles, mumps, rubella] booster and 73% for polio and DPT booster). Age-appropriate timely vaccination coverages were lower than absolutes for all biologics. BCG and hepatitis B had coverages of 97% and Although most vaccination coverages were greater than 90%, probably the mobility restrictions due to the pandemic severely impacted the timing of vaccination. Other plausible reasons are the timely flow of vaccines (opportunity in administration and vaccine shortages).